Analysis of improving Indonesian human resources quality to promote state economic growth - Sembiring, Rasmulia; Sitorus, Sunday Ade (Management and Entrepreneurship: Trends of Development, 2022)
Indonesian human resources have decreased slightly in the last five years. Apart from the Covid-19 pandemic hitting the world of work, the existing human resources do not have good quality. When the Covid-19 pandemic occur, some human resources without competence their expertise are less innovative in creating novel things that can encourage Indonesia to increase economic growth during the Covid-19 Pandemic. In addition, Indonesian human resources lack integrity, so they are unable to improve their abilities during the pandemic and are not trusted by several parties in producing useful products to increase the country’s economic growth. This research employed a descriptive quantitative through multiple linear regression analysis using SPSS 22. The population of this study involved 128,454 workforces in Indonesia. This study used purposive sampling technique to take samples consisting of 100 workers through the distribution of questionnaires to test whether there was an influence of the characteristics of high-quality human resources on the human resources quality in promoting the increase inthe state economic growth. Based on the partial hypothesis, the analys results showed that partially and simultaneously, the variables of Human Resources’ creativities, Human Resources’ innovation, and Human Resources with integrity had a positive and significant impact on improving the quality of Human Resourcers in escalating Indonesian economic growth. JEL Classification: M12, O10, O15.